A Low Mutual Coupling Design for Array Microstrip Antennas Integrated with Electromagnetic Band-Gap Structures. (2016) - Kaabal, Abdelmoumen; halaoui, Mustapha El; Ahyoud, Saida; Asselman, Adel
Abstract: Developing and employing methods to reduce the mutual coupling between elements of an antenna array has become a hot topic in the design of antenna arrays. The utilization of electromagnetic band-gap (EBG) structures is an attractive way to reduce surface wave excitation in printed antenna geometries so to mitigate the mutual coupling problem. This paper investigates the performance of a microstrip antenna phased array embedded in an EBG. A novel EBG array configuration is proposed, the band-gap feature of mushroom-like EBG has been studied, its band-gap feature of surface-wave suppression is demonstrated by plotting variations of the transmission coefficient S12 with frequency and dispersion diagram. The antenna design is verified by High Frequency Structural Simulator (HFSS), the simulating results show that the EBG design approach is a good candidate for a reduction in mutual coupling at certain frequencies between radiator elements, which in turn increases antenna directivity.